Relationship of corporate governance in non-real estate company with corporate real estate acquisition and performance - Wong, Annie Ping Eng, 1987-, author 604559; Lee, Janice Yim Mei, supervisor 494012; Fakulti Geoinformasi Dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2016